Tata Kelola Perusahaan dan Pengungkapan Perbankan Hijau: Peran Moderasi Regulasi Perbankan Hijau - Firmansyah, Amrie; Kartiko, Nafis Dwi (Jurnal Akuntansi dan Bisnis, 2024)
Adegboye, A., Ojeka, S., Alabi, O., Alo, U., & Aina, A. (2020). Audit committee characteristics and sustainability performance in Nigerian listed banks. Business: Theory and Practice, 21(2), 469–476. Adu, D.A., Al‐Najjar, B., & Sitthipongpanich, T. (2022). Executive compensation, environmental performance, and sustainable banking: The moderating effect of governance mechanisms. Business Strategy and the Environment, 31(4), 1439–1463. Akhter, F., Hossain, M.R., Elrehail, H., Rehman, S.U., & Almansour, B. (2022). Environmental disclosures and corporate attributes, from the lens of legitimacy theory: A longitudinal analysis on a developing country. European Journal of Management and Business Economics, 32(3), 342–369. Alfraih, M.M., & Almutawa, A.M. (2017). Voluntary disclosure and corporate governance: empirical evidence from Kuwait. International Journal of Law and Management, 59(2), 217–236. Arayssi, M., Jizi, M., & Tabaja, H.H. (2020). The impact of board composition on the level of ESG disclosures in GCC countries. Sustainability Accounting, Management and Policy Journal, 11(1), 137–161. Bajahar, M.S., & Al-Hajili, A.H. (2017). The impact of the board of directors’ structure on the level of voluntary disclosure in cement companies listed on the Saudi Stock Exchange. Arab Journal of Administrative Sciences, 24(3), 383–410. Baselga-Pascual, L., Trujillo-Ponce, A., Vähämaa, E., & Vähämaa, S. (2018). Ethical reputation of financial institutions: Do board characteristics matter? Journal of Business Ethics, 148, 489–510. Bear, S., Rahman, N., & Post, C. (2010). The impact of board diversity and gender composition on corporate social responsibility and firm reputation. Journal of Business Ethics, 97, 207–221. Ben-Amar, W., Chang, M., & McIlkenny, P. (2017). Board gender diversity and corporate response to sustainability initiatives: Evidence from the carbon disclosure project. Journal of Business Ethics, 142(2), 369–383. Bhardwaj, B.R., & Malhotra, A. (2013). Green banking strategies: Sustainability through corporate entrepreneurship. Greener Journal of Business and Management Studies, 3(4), 180–193. Bhatia, S., & Marwaha, D. (2022). The influence of board factors and gender diversity on the esg disclosure score: A study on Indian companies. Global Business Review, 23(6), 1544–1557. Birindelli, G., Dell’Atti, S., Iannuzzi, A.P., & Savioli, M. (2018). Composition and activity of the board of directors: Impact on ESG performance in the banking system. Sustainability, 10(12), 4699. Bose, S., Khan, H. Z., Rashid, A., & Islam, S. (2018). What drives green banking disclosure? An institutional and corporate governance perspective. Asia Pacific Journal of Management, 35(2), 501–527. Buallay, A., Hamdan, R., Barone, E., & Hamdan, A. (2022). Increasing female participation on boards: Effects on sustainability reporting. International Journal of Finance & Economics, 27(1), 111–124. Budiharta, P., & Kacaribu, H.E.P.B. (2020). The influence of board of directors, managerial ownership, and audit committee on carbon emission disclosure: A study of non-financial companies listed on BEI. Review of Integrative Business and Economics Research, 9, 75–87. Chen, X., & Chen, Z. (2021). Can green finance development reduce carbon emissions? Empirical evidence from 30 Chinese Provinces. Sustainability, 13(21), 12137. Chen, Z., Mirza, N., Huang, L., & Umar, M. (2022). Green banking—Can financial institutions support green recovery? Economic Analysis and Policy, 75, 389–395. Crossley, R.M., Elmagrhi, M.H., & Ntim, C.G. (2021). Sustainability and legitimacy theory: The case of sustainable social and environmental practices of small and medium‐sized enterprises. Business Strategy and the Environment, 30(8), 3740–3762. Dewi, I., & Dewi, I. (2017). Corporate social responsibility, green banking, and going concern on banking company in Indonesia stock exchange. International Journal of Social Sciences and Humanities, 1(3), 118–134. Diamastuti, E., Muafi, M., Fitri, A., & Faizaty, N.E. (2021). The role of corporate governance in the corporate social and environmental responsibility disclosure. The Journal of Asian Finance, Economics and Business, 8(1), 187–198. Didier, T., Huneeus, F., Larrain, M., & Schmukler, S.L. (2021). Financing firms in hibernation during the COVID-19 pandemic. Journal of Financial Stability, 53, 100837. Farida, D.N., & Purwanto, A. (2021). Do board characteristics impact green banking disclosure? Empirical evidence from Indonesia. Indonesian Journal of Sustainability Accounting and Management, 5(2), 187-197. Fine, C., Sojo, V., & Lawford‐Smith, H. (2020). Why does workplace gender diversity matter? Justice, organizational benefits, and policy. Social Issues and Policy Review, 14(1), 36–72. Firmansyah, A., & Kartiko, N.D. (2024). Exploring the association of green banking disclosure and corporate sustainable growth: the moderating role of firm size and firm age. Cogent Business and Management, 11(1), 1–18. García‐Sánchez, I., Martínez‐Ferrero, J., & García‐Meca, E. (2018). Board of directors and CSR in banking: The moderating role of bank regulation and investor protection strength. Australian Accounting Review, 28(3), 428–445. Gavrilko, T., & Pobochenko, L. (2021). Environmentalization and the green economy in the perspective of future generations. Green banking as a tool for implementing the model of a socially responsible banking institution. Baltija Publishing, 442–460. Ghio, A., & Verona, R. (2020). Voluntary corporate disclosure. The Evolution of Corporate Disclosure: Insights on Traditional and Modern Corporate Communication. Springer, 55–100. Gianie, G. (2022). Analisis litbang ”kompas”: Perbankan hijau untuk ekonomi hijau. Kompas. Diakses dari https://www.kompas.id/ Glass, C., & Cook, A. (2018). Do women leaders promote positive change? Analyzing the effect of gender on business practices and diversity initiatives. Human Resource Management, 57(4), 823–837. Gunawan, J., Permatasari, P., & Sharma, U. (2022). Exploring sustainability and green banking disclosures: A study of banking sector. Environment, Development and Sustainability, 24(9), 11153–11194. Handojo, N.T.A., Machmuddah, Z., & Sumaryati, A. (2023). Independent board of commissioners moderates CSR disclosure relationship on financial performance. Indonesian Journal Of Sustainability, 1(2), 45–55. Helfaya, A., & Moussa, T. (2017). Do board’s corporate social responsibility strategy and orientation influence environmental sustainability disclosure? UK evidence. Business Strategy and the Environment, 26(8), 1061–1077. Hossain, D.M., Bir, A., Sadiq, A.T., Tarique, K.M., & Momen, A. (2016). Disclosure of green banking issues in the annual reports: a study on Bangladeshi banks. Middle East Journal of Business, 11(1), 19–30. Husna, A., & Satria, I. (2019). Effects of return on asset, debt to asset ratio, current ratio, firm size, and dividend payout ratio on firm value. International Journal of Economics and Financial Issues, 9(5), 50–54. Inderst, G., & Stewart, F. (2018). Incorporating environmental, social and governance (ESG) factors into fixed income investment. World Bank Group publication. Islam, M.S., & Das, P.C. (2013). Green banking practices in Bangladesh. IOSR Journal of Business and Management, 8(3), 39–44. Itan, I., & Khelen, K. (2022). Role of risk management in independent commissioners and audit committees on financial performance. Global Financial Accounting Journal, 6(2), 225–236. Kanakriyah, R. (2016). Voluntary disclosure and its effect on the quality of accounting information according to users’ perspective in Jordan. American Journal of Business, Economics and Management, 4(6), 134–146. Karyani, E., & Obrien, V.V. (2020). Green banking and performance: the role of foreign and public ownership. Jurnal Dinamika Akuntansi dan Bisnis, 7(2), 221–234. Khalil, M.A., & Nimmanunta, K. (2022). Conventional versus green investments: Advancing innovation for better financial and environmental prospects. Journal of Sustainable Finance & Investment, 1–28. Khan, H.Z., Bose, S., Sheehy, B., & Quazi, A. (2021). Green banking disclosure, firm value and the moderating role of a contextual factor: Evidence from a distinctive regulatory setting. Business Strategy and the Environment, 30(8), 3651–3670. Khan, P.A., Johl, S.K., & Johl, S.K. (2021). Does adoption of ISO 56002‐2019 and green innovation reporting enhance the firm sustainable development goal performance? An emerging paradigm. Business Strategy and the Environment, 30(7), 2922–2936. Kouaib, A., Mhiri, S., & Jarboui, A. (2020). Board of directors’ effectiveness and sustainable performance: The triple bottom line. The Journal of High Technology Management Research, 31(2), 100390. Liao, L., Luo, L., & Tang, Q. (2015). Gender diversity, board independence, environmental committee and greenhouse gas disclosure. The British Accounting Review, 47(4), 409–424. Mahfuzur, R.S.M., & Barua, S. (2016). The design and adoption of green banking framework for environment protection: Lessons from Bangladesh. Australian Journal of Sustainable Business and Society, 2(1), 1–19. Mahmood, Z., Kouser, R., Ali, W., Ahmad, Z., & Salman, T. (2018). Does corporate governance affect sustainability disclosure? A mixed methods study. Sustainability, 10(1), 207. Mahrani, M., & Soewarno, N. (2018). The effect of good corporate governance mechanism and corporate social responsibility on financial performance with earnings management as mediating variable. Asian Journal of Accounting Research, 3(1), 41–60. Manita, R., Bruna, M.G., Dang, R., & Houanti, L. (2018). Board gender diversity and ESG disclosure: evidence from the USA. Journal of Applied Accounting Research, 19(2), 206–224. Michael, A., & Dixon, R. (2019). Audit data analytics of unregulated voluntary disclosures and auditing expectations gap. International Journal of Disclosure and Governance, 16, 188–205. Muthitacharoen, A. (2020). Assessing tax burden differential between foreign multinationals and local firms: Implications for FDI tax incentives. Diakses dari https://www.pier.or.th/ Naciti, V. (2019). Corporate governance and board of directors: The effect of a board composition on firm sustainability performance. Journal of Cleaner Production, 237. Nasih, M., Harymawan, I., Paramitasari, Y.I., & Handayani, A. (2019). Carbon emissions, firm size, and corporate governance structure: Evidence from the mining and agricultural industries in Indonesia. Sustainability, 11(9), 1–14. Oba, V.C., & Fodio, M.I. (2014). Board characteristics and the quality of environmental reporting in Nigeria. The Journal of Accounting and Management, 2(2), 33–48. Park, H., & Kim, J.D. (2020). Transition towards green banking: role of financial regulators and financial institutions. Asian Journal of Sustainability and Social Responsibility, 5(1), 1–25. Petro, S., Octavia, R., & Diarsyad, M.I. (2023). Pengaruh corporate governance terhadap green banking disclosure (Studi pada perusahaan perbankan di Indonesia yang terdaftar di BEI Periode 2018-2020). Jurnal Ilmiah Ekonomi Global Masa Kini, 14(1), 7–14. Pozzoli, M., Pagani, A., & Paolone, F. (2022). The impact of audit committee characteristics on ESG performance in the European Union member states: Empirical evidence before and during the COVID-19 pandemic. Journal of Cleaner Production, 371, 133411. Pratiwi, A., Basyith, A., & Safitri, E. (2023). Disclosure of green banking, profitability and company size on company value in banking in Indonesia. International Journal of Finance Research, 4(2), 115–127. Qa’dan, M.B.A., & Suwaidan, M.S. (2018). Board composition, ownership structure and corporate social responsibility disclosure: The case of Jordan. Social Responsibility Journal, 15(1), 28–46. Rahmiati, A., & Agustin, H. (2022). Pengaruh dewan komisaris independen, komite audit, dan kepemilikan asing terhadap green banking disclosure (Studi pada perbankan di Indonesia tahun 2017-2021). Wahana Riset Akuntansi, 10(2), 165–179. Rudyanto, A., & Siregar, S.V. (2018). The effect of stakeholder pressure and corporate governance on the sustainability report quality. International Journal of Ethics and Systems, 34(2), 233–249. Sharma, M., & Choubey, A. (2022). Green banking initiatives: A qualitative study on Indian banking sector. Environment, Development and Sustainability, 24(1), 293–319. Suchanek, A. (2020). The problem of corporate legitimacy. In Handbook of business legitimacy. Springer, 31–52. Suchman, M.C. (1995). Managing legitimacy: Strategic and institutional approaches. Academy of Management Review, 20(3), 571–610. Sun, H., Rabbani, M.R., Ahmad, N., Sial, M.S., Cheng, G., Zia-Ud-Din, M., & Fu, Q. (2020). CSR, co-creation and green consumer loyalty: Are green banking initiatives important? A moderated mediation approach from an emerging economy. Sustainability, 12(24), 10688. Taskinsoy, J. (2019). Ever more financial instability notwithstanding the Basel standards and the IMF’s financial sector assessment program. Diakses dari https://papers.ssrn.com/ Tauringana, V., & Chithambo, L. (2015). The effect of DEFRA guidance on greenhouse gas disclosure. The British Accounting Review, 47(4), 425–444. Temiz, H., & Acar, M. (2023). Board gender diversity and corporate social responsibility (CSR) disclosure in different disclosure environments. Corporate Social Responsibility and Environmental Management, 30(5), 2247-2264 Ullah, M.H., & Mia, P. (2020). How green is the green banking investment in Bangladesh?: a paradox of green banking practices. Global Approaches to Sustainability Through Learning and Education, 270–280). IGI Global. Wang, M., Li, Y., & Wang, Z. (2023). A nonlinear relationship between corporate environmental performance and economic performance of green technology innovation: Moderating effect of government market‐based regulations. Business Strategy and the Environment, 32(6), 3119–3138. Wasiuzzaman, S., & Wan Mohammad, W.M. (2020). Board gender diversity and transparency of environmental, social and governance disclosure: Evidence from Malaysia. Managerial and Decision Economics, 41(1), 145–156. Winarto, W.W.A., Nurhidayah, T., & Sukirno, S. (2021). Pengaruh green banking disclosure terhadap nilai perusahaan pada bank umum syariah di Indonesia. Velocity: Journal of Sharia Finance and Banking, 1(2), 12–22. Yadav, R., & Pathak, G. (2013). Environmental sustainability through green banking: A study on private and public sector banks in India. OIDA International Journal of Sustainable Development, 6(8), 37–48. Yip, A. W. H., & Bocken, N.M.P. (2018). Sustainable business model archetypes for the banking industry. Journal of Cleaner Production, 174, 150–169. Yoon, B., Lee, J.-H., & Cho, J.-H. (2021). The effect of esg performance on tax avoidance-evidence from Korea. Sustainability, 13(12), 1–16. Zhang, W., Hong, M., Li, J., & Li, F. (2021). An examination of green credit promoting carbon dioxide emissions reduction: a provincial panel analysis of China. Sustainability, 13(13), 1–21.